Pengaruh Literasi Keuangan, Gaya Hidup Dan Pendidikan Keuangan Dalam Keluarga Terhadap Pengelolaan Keuangan Pribadi Mahasiswa Pendidikan Ekonomi UNS - Moh Amin Yusuf; Sudarno Sudarno; Salman Alfarisy Totalia (Departement of Mathematics Education, 2023)
This research aims to determine the effect of financial literacy, lifestyle and financial education in the family on the personal financial management of Economics Education students at UNS class of 2018 and 2019 both partially and simultaneously. This research is a quantitative study with a population of 2018 and 2019 UNS Economics Education students with a total sample of 110 respondents. Collecting data using a questionnaire and analyzing data using multiple linear regression analysis. The results showed that (1) there is a positive and significant influence between financial literacy on personal financial management of UNS Economics students 2018 and 2019 (2) there is a positive and significant influence between lifestyle on personal financial management of UNS Economics students 2018 and 2019 (3) there is a positive and significant influence between financial education in the family on the personal financial management of UNS Economics students class of 2018 and 2019 (4) there is a positive and significant effect between financial literacy, lifestyle and financial education in the family on the personal financial management of Education students UNS Economics Class of 2018 and 2019.